Social Innovation Toward a Meaningful Everyday Life for Nursing Home Residents: An Ethnographic Study - Slettebø, Åshild; Skaar, Ragnhild; Brodtkorb, Kari (Frontiers in Psychology, 2021)
Background: The literature shows that innovation, which includes culture change, may be important to create a meaningful everyday life for nursing home residents. However, there is a gap in how social innovation practices may contribute to this. The theoretical discourse for the study is person-centred care. Aim: The main aim was to explore phenomena within social innovation that can contribute to improving nursing home residents’ everyday lives. Design and Method: This study uses an ethnographic design with observations and interviews in two nursing homes in Southern Norway. Findings: The main theme was that social innovation within working practices in nursing homes includes phenomena that contribute to a meaningful everyday life for the residents. This main theme includes five subthemes: (1) opening the nursing home to the surroundings; (2) expanding and strengthening the community of practice; (3) facilitating customized activities; (4) ensuring sufficient nutrition and facilitating enjoyable mealtimes; and (5) preventing unrest and disturbing behavior. Conclusion: The study reveals that innovation practices grounded in person-centred care in nursing homes may contribute to opening the nursing home to the community and establishing a common community practice for all members of the nursing home. This enables residents to experience meaningful everyday life through customized activities, sufficient nutrition, and a pleasant milieu during mealtimes. Disturbing behavior is also prevented, making it possible to promote meaningful lives in nursing homes.